Environmental-Based Coffee Agroforestry Development Strategy in Pujon Forest Area - Bilqis, Melinda; Putra , M. Ardian Permana; Purba, Kenny Prizky; Faizah, Fifi Nur (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Agroforestry for coffee in the Pujon forest area needs development considering the importance of community well-being and livelihoods around the forest. Additionally, the forest environment must be preserved to prevent natural disasters in the surrounding areas. The main purpose of this research is to identify strengths that can be enhanced, evaluate weaknesses that need improvement, explore opportunities for development, and identify threats that need to be addressed in the context of environmentally based agroforestry in the Pujon forest area. The location was intentionally chosen in the Pujon subdistrict, Malang City. The Pujon forest area was selected for the study because the local community utilizes the land by growing vegetables, which increases the potential for natural disasters. The IFE matrix, EFE matrix, and SWOT analysis were applied. The IFE analysis yielded scores of 1.71 for strengths and 1.52 for weaknesses. Meanwhile, the EFE analysis scored 1.79 for opportunities and 1.64 for threats. The SWOT matrix analysis indicates that the strategy for developing environmentally based coffee agroforestry in the Pujon forest area falls within quadrant I. Therefore, the recommended strategy is to provide moral and material support to farmers who are willing to cultivate coffee plants, aiming to reduce the potential for natural disasters and utilize productive land.